Between reason and revelation : twin wisdoms reconciled : an annotated English translation of Nasir-i Khusraw's Kitab-i Jami al-ḥikmatayn /: twin wisdoms reconciled : an annotated English translation of Nasir-i Khusraw's Kitab-i Jami al-ḥikmatayn. (2012) - Unknown
No abstract available